In-plane cyclic performance of adobe walls retrofitted with near-surface-mounted steel rebars. (1st September 2019) - Mirabi Banadaki, Hosein; Morshed, Reza; Eslami, Abolfazl
Highlights: Seismic retrofit of in-plane loaded adobe walls. Walls were subject to loads and displacements. Retrofit scheme is comprised of NSM steel rebars. Results are compared in terms of load-displacement capacity, ductility, and displacement capacity. Abstract: Vulnerability of adobe constructions under lateral loading has promoted efforts to explore a wide variety of techniques for their retrofitting. Following this trend, the present experimental study was designed and implemented to investigate in-plane lateral strengthening/repairing of adobe walls using near-surface-mounted (NSM) steel rebars. The experimental parameters were comprised of reinforcement ratio, axial pre-compression load, and initial damage. For this purpose, seven wall panels, including two control, two repaired, and three strengthened panels, were made of identical adobe units and mud mortar. All walls have a thickness of 200 mm, a length of 1020 mm, and an effective height of 700 mm. Testing was performed under an incremental lateral displacement reversals combined with a constant pre-compression axial load. The experiment was designed such that the as-built specimens would undergo their failure mode in the form of diagonal shear cracking. This provision was allowed the proper assessment of the adopted NSM retrofitting technique in terms of its efficiency to preventing this undesirable failure mode. Finally, the results were compared based on the hysteretic load-displacement curves and other structural parameters. The adopted technique was found to be effective not only in strengthening existing adobe walls, but also in rehabilitating significantly damaged ones.